2011
DOI: 10.1002/jor.21539
|View full text |Cite
|
Sign up to set email alerts
|

The gliding characteristics of the flexor pollicis longus tendon in the carpal tunnel: Potential implications for manual pipette users

Abstract: To understand the potential mechanism for hand and wrist complaints in pipette users, whose motion is characterized by repetitive thumb motion in certain wrist positions, the peak (PGR) and mean (MGR) gliding resistance of the flexor pollicis longus (FPL) tendon were measured in nine human cadaver wrists. The PGR with the wrist in 308 ulnar deviation and in the neutral position were significantly lower than the PGR with the wrist in 608 flexion. The MGR with the wrist in 308 ulnar deviation was significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The finding that the powerful thenar muscles span to over 50% of the TCL on the radial side indicates that in healthy subjects, the muscle-ligament interface predisposes the TCL for tissue remodeling when biomechanical interaction frequently occurs during manual activities of daily life, including those associated with several occupations such as piano playing and pipetting. 2,3 In particular, the radial half of the TCL is connected with the powerful thenar muscles and could undergo thickening and stiffening after prolonged, repetitive thumb activities. The median nerve, closely abutted with the TCL in the radial region, can be particularly vulnerable to compression neuropathy under increased mechanical constraint caused by tissue maladaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that the powerful thenar muscles span to over 50% of the TCL on the radial side indicates that in healthy subjects, the muscle-ligament interface predisposes the TCL for tissue remodeling when biomechanical interaction frequently occurs during manual activities of daily life, including those associated with several occupations such as piano playing and pipetting. 2,3 In particular, the radial half of the TCL is connected with the powerful thenar muscles and could undergo thickening and stiffening after prolonged, repetitive thumb activities. The median nerve, closely abutted with the TCL in the radial region, can be particularly vulnerable to compression neuropathy under increased mechanical constraint caused by tissue maladaptation.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that the thenar muscles activate to pull the TCL volarly during a pinch movement, 1 and this repeated in vivo tissue mechanics could lead to hypertrophy of the involved muscles and ligament. The TCL is known to remodel to become thicker under repetitive, prolonged use of thumb as associated with pipetting 2 and piano playing. 3 A thickened TCL as a result could compress the median nerve and eventually lead to carpal tunnel syndrome.…”
mentioning
confidence: 99%